Pelatihan Model Kepemimpinan Kepala Sekolah Mengimplementasikan Learning Organization untuk Mencapai Sekolah Efektif di Kabupaten Pringsewu - Riswandi; Lungit Wicaksono; Mujiyati; Fadhilah Khairani (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2022)
Learning organization is an important aspect in achieving organizational success which is carried out by a group of people with the same goals. A learning organization should have been implemented at every school level. The purpose of carrying out this service activity is to provide understanding and knowledge and readiness that must be designed to achieve effective schools in elementary schools in Pringsewu Regency. So that the specific target to be achieved is that participants can implement a learning organization to achieve effective schools through the principal's leadership model. The methods used are (1) discourse; present analysis of various related government regulations; (2) brainstorming and discussion; explore information on participants' understanding and what has been done; (3) role playing; improve the management ability of participants; and (4) analysis of the documents needed to design effective schools. The targets of this activity are principals and elementary school teachers in Pringsewu Regency. The results of community service activities obtained an average post-test of 88, higher than the pre-test which was 53.85. So the average percentage is 64.23%. Based on the results of the evaluation of activities, it is recommended that such training be followed up by expanding the target audience to design effective schools in elementary school.